Ehrlichia, Hepatozoon, and Babesia Coinfection Patterns Among Owned Dogs in Central Thailand - Rungrote Osathanon; Aeknarin Saechin; Chalisa Mongkolphan; Benjaporn Bhusri; Siriporn Tangsudjai (Journal of Veterinary Internal Medicine)
ABSTRACT Background Ehrlichia, Hepatozoon, and Babesia have the potential to cause life‐threatening illnesses in dogs, especially when coinfections occur. Hypothesis/Objectives To determine the infection rates, coinfection patterns, and risk factors associated with these pathogens in central Thailand. Animals Two thousand five hundred nineteen owned dogs presented with clinical abnormalities consistent with tick‐borne diseases between 2019 and 2023. Methods Retrospective study, blood samples were analyzed using multiplex PCR to assess infection rates. The study compared infection rates across different sexes and age groups and tracked monthly variations. Results A total of 19.02% (95% CI: 17.50–20.60) of dogs were infected by one pathogen infection: Ehrlichia 11.47% (10.25–12.78), Babesia 2.78% (2.17–3.50), and Hepatozoon 1.83% (1.34–2.43). Infections occurred year‐round but peaked in May. Coinfections were observed in 2.94% (2.31–3.67) of cases. Among infected dogs, coinfections were identified in 34% (36/106) and 53% (52/98) of dogs with babesiosis or hepatozoonosis, respectively, whereas 19% (69/358) of dogs with ehrlichiosis were co‐infected. Coinfections peaked in April, occurred in all age groups, and were more frequent in dogs younger than 1 year compared to dogs older than 7 years. Conclusions and Clinical Importance These findings underscore the importance of comprehensive diagnostic testing for multiple pathogens and tick prevention in dogs living in this region.